A Novel Papr Reduction Approach Based On The Weighted OFDM Algorithm (International Journal of Engineering and Computer Science, 2017)
Although tremendous progress has been made in the area of wireless communications based on orthogonal frequency division multiplexing but still there exist some problems. In literature so many works has been reported to resolve the issues but still Peak to average power ratio is still area of concern. In this paper, instead of spectral efficiency we make use of HPA (high power amplifier) weights to resolve the issue of Peak to average power ratio. Meanwhile, the time period required to transmit the weighted OFDM signal is that the same because the time period for the first OFDM signal. The performance of the proposed scheme is estimated with Mat lab Simulator. With respect to the theoretical analysis, the weighted OFDM signal PAPR is smaller than that of the clipping and filtering (C&F) methodology, and also the bit-error-rate (BER) performance of the weighted OFDM system is improved compared with the C&F methodology. Here, the projected methodology is easier than the C&F method.